Konstruksi Berita Layanan Publik Dalam Program "Sumut Dalam Berita" TVRI Sumatera Utara - Feby Grace Adriany (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2018)
This research is conducted to determine the construction of public service news in ‘Sumut Dalam Berita’ program aired on TVRI North Sumatera. With the phenomenological approach, this research used Theories of Influences on Mass Media Content by Pamela J. Shoemaker and Stephen D. Reese. This study conducted an in-depth interview with an internal level of TVRI North Sumatera that is managerial level and the external party who cooperate with TVRI that is North Sumatera Provincial Government.  The results show that : (1) public service news is being a part of the cooperation between TVRI North Sumatera and the Provincial Government. TVRI also receive funds from local budgets for operations activities, (2) each level of the influence of media content starting from individual level to ideological level contributes to public service news production in ‘Sumut Dalam Berita.’ Sometimes there are overlaping between the ideal and practical concepts experienced by the journalist in delivering public information to the public. The contribution of this research is to give insight to journalists and editors on how to produce news, especially on public services without ignoring news value.